Towards Effective Adaptive Revision: Comparative Analysis of Online Assessment Platforms through the Combined AHP-MCDM Approach - Smahi, Kaoutar; Labouidya, Ouidad; El Khadiri, Khalid (International Journal of Interactive Mobile Technologies (iJIM), 2024)
This study presents a detailed comparative analysis of online evaluation platforms aimed at identifying the most suitable one for integrating an adaptive revision plugin. The study uses both the analytic hierarchy process (AHP) and multi-criteria decision making (MCDM) to give a structured and thorough evaluation of different learning management systems (LMSs). By scrutinizing the capabilities, interfaces, and underlying technologies of these systems, the analysis seeks to pinpoint the platform that offers optimal compatibility, flexibility, functionality, and user experience. The central objective of this study is to enhance the effectiveness of adaptive learning tools within educational technologies. This is achieved by evaluating different platforms to ascertain which one best supports the integration of adaptive revision functionalities. Our comprehensive analysis clearly identifies Moodle as the superior platform due to its robust adaptability and enhanced customization capabilities, which are essential for implementing effective adaptive learning tools. The results underscore Moodle’s potential to significantly enhance the educational experience by supporting tailored learning paths and dynamic content adjustments. This study not only highlights Moodle’s advantages but also sets the groundwork for future advancements in adaptive educational technologies.